PERAN DAN FUNGSI KODE ETIK KEPRIBADIAN GURU DALAM PENGEMBANGAN PENDIDIKAN - Marjuni, Andi (Jurnal Pendidikan Kreatif, 2020)
Teacher as a professional educator with the main responsibility of educating, teaching, guiding, directing, training, and evaluating students in earlier, formal, basic, and secondary education. Teacher code of ethics was established in a congress attended by all delegates and regional administrators of PGRI (Indonesian Teacher Association) throughout Indonesia at the 13th congress in Jakarta in 1973, which was later refined at the16th PGRI congress in 1989 in Jakarta as follows: Teachers are responsible to guide students have the soul of Pancasila, they implement honesty professionalism, they also search information as guiding and coaching material, teachers create well atmosphere at school to support the success of teaching and learning process, they maintain good relationship to the students' parents and surrounding communities to foster their participation and responsibility for education, and the teachers personally and jointly develop and improve the quality and dignity of their profession.